‘It's not what it looks like. I'm Santa’: connecting community through film - Jones, Susan; McIntyre, Joanna (Taylor & Francis, 2014)
The lived experiences of young people are becoming increasingly marginalised within the narrowly defined curricula of neoliberal contexts. Many young people are also cast within the media according to deficit discourses of youth which contribute to the fragmentation of communities and the limitation of interaction between generations. This article describes a film project in which young people living in an ex-mining community in the midlands of England worked in and with their community to create a representation of where they live. As part of the process, the young film-makers did more than connect to other people’s memories as repositories of information; both as process and as product, their film can be seen to connect shared narratives of people and place, across time and space. We argue that this project offers a timely opportunity to reflect upon the ways in which we understand learning in and out of English classrooms.